The shards [large type] - Ellis, Bret Easton (Thorndike Press, a part of Gale, a Cengage Company, 2023)
"Seventeen-year-old Bret is a senior at the exclusive Buckley prep school when a new student arrives with a mysterious past. Robert Mallory is bright, handsome, charismatic, and shielding a secret from Bret and his friends even as he becomes a part of their tightly knit circle. Bret's obsession with Mallory is equaled only by his increasingly unsettling preoccupation with the Trawler, a serial killer on the loose who seems to be drawing ever closer to Bret and his friends, taunting them--and Bret in particular--with grotesque threats and horrific, sharply local acts of violence. The coincidences are uncanny, but they are also filtered through the imagination of a teenager whose gifts for constructing narrative from the filaments of his own life are about to make him one of the most explosive literary sensations of his generation. Can he trust his friends--or his own mind--to make sense of the danger they appear to be in? Thwarted by the world and by his own innate desires, buffeted by unhealthy fixations, he spirals into paranoia and isolation as the relationship between the Trawler and Robert Mallory hurtles inexorably toward a collision" --